Sintesis Polianilin (PANI) yang di Doping Besi (III) Oksida Menggunakan Metode Fotopolimerisasi - Nofianti, Nora; Ulianas, Alizar; Kurniawati, Desy (Departemen Kimia FMIPA UNP, 2023)
This study aims to increase the electrical conductivity of the aniline synthesis product with added dopant. Polyaniline conductive polymer synthesis was carried out with aniline monomer mixed with Ethylene Glycol Dimethacrylate (EGDMA) as crosslinker, Dimethoxy phenylacetophenone (DMPP) as initiator, Fe2O3 as dopant. The polymer results were tested for electrical conductivity using a Four Point Probe (FPP) and characterized by Fourier Transform Infrared (FTIR), Uv-vis DRS (Uv-visible Diffuse Reflectance). the composition that showed the highest conductivity was the addition of Fe2O3 dopant as much as 0.0283 g with an electrical conductivity value of 17.0609 x 10-3 S/cm.